Investigating perceptions and support for transparency and openness in research: Using card sorting in a pilot study with academic librarians. Issue 1 (27th December 2016) - Lyon, Liz; Mattern, Eleanor; Jeng, Wei; He, Daqing
ABSTRACT: This paper explores the role of academic librarians as advocates for research transparency and open research. We describe the design and piloting of a qualitative card‐sorting research protocol that investigates academic librarians' attitudes, awareness and practices related to research transparency. We report on preliminary results from interviews with librarians, presenting their conceptualizations of research transparency and open research, existing library services that support and advocate for both concepts, and potential services that would augment this support and advocacy. Library activities they feel are most important to the advancement of transparency and openness are identified and perceptions of disciplinary differences are noted.